2009
DOI: 10.1210/en.2009-0066
|View full text |Cite
|
Sign up to set email alerts
|

Trefoil Factor-1 (TFF1) Enhances Oncogenicity of Mammary Carcinoma Cells

Abstract: The functional role of autocrine trefoil factor-1 (TFF1) in mammary carcinoma has not been previously elucidated. Herein, we demonstrate that forced expression of TFF1 in mammary carcinoma cells resulted in increased total cell number as a consequence of increased cell proliferation and survival. Forced expression of TFF1 enhanced anchorage-independent growth and promoted scattered cell morphology with increased cell migration and invasion. Moreover, forced expression of TFF1 increased tumor size in xenograft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 60 publications
0
49
0
Order By: Relevance
“…Both GREB1 and TFF1 are strongly correlated with ER protein expression and are required for E2-induced proliferation and invasion of ERϩ breast cancer cells. 21,32,33 TRIM29 is able to independently induce these ER-regulated genes, but the level of induction is reduced in the presence of E2, accounting for the observed tumor suppressor effects.…”
Section: Discussionmentioning
confidence: 99%
“…Both GREB1 and TFF1 are strongly correlated with ER protein expression and are required for E2-induced proliferation and invasion of ERϩ breast cancer cells. 21,32,33 TRIM29 is able to independently induce these ER-regulated genes, but the level of induction is reduced in the presence of E2, accounting for the observed tumor suppressor effects.…”
Section: Discussionmentioning
confidence: 99%
“…Amiry et al showed that TFF1 functioned as an oncogene and forced expression of TFF1 increased the oncogenicity of human breast cancer MCF7 and T47D cells [68]. On the contrary, Buache et al reported TFF1 acted as a beneficial factor rather than an oncogene in the breast and knockout of TFF1 augmented the tumorigenicity of breast cancer cells and stimulated breast tumor development [69]. Although TFF1 enhanced the migration and invasion of breast cancer MDA-MB-231, MCF7 and ZR75.1 cells under in vitro conditions, its expression is usually depleted in highly metastatic breast cancer cell lines such as MDA-MB-231 [69].…”
Section: Riz1 Exerts Its Histone Modification Functions Via Binding Tmentioning
confidence: 99%
“…Extraction of RNA and semiquantitative RT-PCR RNA extraction and semiquantitative reverse transcriptase (RT)-PCR was carried out as described previously (Amiry et al 2009). Amplified RT-PCR products were visualised on a 1.5% agarose gel.…”
Section: Cell Lines and Cell Transfectionmentioning
confidence: 99%
“…Cell growth in the basement membrane extract, Matrigel, was assayed as described previously (Amiry et al 2009). Briefly, RL95-2, T47D and MDA-MB-435S cells were suspended in 4% growth factor reduced Matrigel (BD Biosciences, San Jose, CA, USA) in 5% serum media in 96-well plates at 1000 cells/well.…”
Section: D Matrigel Assaymentioning
confidence: 99%